Selective PKCalpha inhibition uncouples platelet angiogenesis promotion from collagen-induced aggregation - RADOMSKI, MAREK (My University, 2013)
Platelets promote angiogenesis by releasing angiogenesis-regulating factors from their α-granules upon aggregation. This effect has both physiologic and pathologic significance as it may contribute to carcinogenesis. Platelet α-granule release and aggregation are regulated, in part, via protein kinase C (PKC) α and β signaling. Our study investigated the effects of PKC inhibition on aggregation, angiogenesis-regulator secretion from α-granules, and platelet-stimulated angiogenesis. We hypothesized that selective PKCα inhibition may preferentially suppress angiogenesis-regulator secretion from α-granules but not aggregation, limiting platelet-stimulated angiogenesis. Human platelets were aggregated in the presence of conventional PKC inhibitors myr-FARKGALRQ and Ro 32-0432 (2-{8-[(dimethylamino)methyl]-6,7,8,9-tetrahydropyridol[1,2-α]indol-3-yl}-3-(1-methyl-1H-indol-3-yl)maleimide). Immunofluorescence microscopy of PKC translocation was used to determine the specificity of PKC-inhibitor targeting. Enzyme-linked immunosorbent assay was used to measure vascular endothelial growth factor (VEGF) and thrombospondin-1 (TSP-1) release from platelets. Platelet effects on angiogenesis were tested using a capillary-formation assay. Ro 32-0432, but not the peptide inhibitor myr-FARKGALRQ (myristoylated-pseudosubstrate peptide inhibitor), inhibited aggregation in a concentration-dependent manner, while both Ro 32-0432 and myr-FARKGALRQ preferentially suppressed VEGF over TSP-1 secretion. Suppression of angiogenesis-regulator release occurred at inhibitor concentrations that did not significantly affect aggregation. Immunofluorescence microscopy revealed that PKCα targeting to α-granules is inhibited when angiogenesis-regulator secretion is uncoupled from aggregation. At concentrations that uncoupled α-granule release from aggregation, Ro 32-0432 and myr-FARKGALRQ inhibited platelet-stimulated angiogenesis. Hence, selective PKCα inhibition suppresses angiogenesis-regulator release from platelet α-granules with minimal effects on aggregation. Thus, selective PKCα inhibitors may have pharmacologic significance to regulate platelet-promoted angiogenesis.
PUBLISHED
Keywords: Platelets